2005
DOI: 10.1080/13697130500196866
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for type 2 diabetes in women attending menopause clinics in Italy: a cross-sectional study

Abstract: This large cross-sectional study suggests that postmenopausal women are at higher risk of type 2 diabetes after allowance for the effect of age. Other main determinants of risk of type 2 diabetes in women around menopause were low socioeconomic status and being overweight. Diabetes was found less frequently in those taking hormone replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Previous results regarding menopausal age are mixed (1214). In a large study among women entering menopause clinics, no association between menopausal age and type 2 diabetes was found (13). In another cross-sectional study, diabetes was more prevalent among women with premature menopause, but this association was not statistically significant after multivariable adjustment (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results regarding menopausal age are mixed (1214). In a large study among women entering menopause clinics, no association between menopausal age and type 2 diabetes was found (13). In another cross-sectional study, diabetes was more prevalent among women with premature menopause, but this association was not statistically significant after multivariable adjustment (14).…”
Section: Discussionmentioning
confidence: 99%
“…Oophorectomized women seem to have less favorable glucose and insulin levels (10,11), which is suggestive of a link between premature menopause and diabetes risk. However, the few epidemiological studies that have investigated the relationship between menopausal age and diabetes yielded conflicting results with either an inverse (12) or no (13,14) association. Thus far, no prospective studies have been performed, and no studies have examined the relationship with reproductive life span (defined as menopausal age minus menarcheal age), which is a marker of total duration of endogenous estrogen exposure.…”
mentioning
confidence: 99%
“…Only one study quantified VAT in overweight and obese women to assess mechanistic links between CRF and metabolism (25). Yet, obese women are prone to develop metabolic disease (20,31). Given the discrepancy among studies, we suggest that VAT may not be the crucial factor linking CRF and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association of menopausal status and hyperglycemia has been investigated ( 4 12 ), findings about whether the postmenopausal state would influence hyperglycemia independently of normal aging remain controversial. Two cohort studies with a large number of female participants investigated the impact of the postmenopausal state on diabetes compared with the premenopausal state ( 13 , 14 ). A study of 22,426 Japanese women suggested that there is no significant association between the postmenopausal state and diabetes when adjustment is made for chronological age ( 14 ).…”
mentioning
confidence: 99%